2005
DOI: 10.1128/aac.49.2.556-559.2005
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Recombinant Influenza A (H1N1) Viruses Harboring Amantadine Resistance Mutations

Abstract: The emergence of resistance to amantadine in influenza A viruses has been shown to occur rapidly during treatment as a result of single-amino-acid substitutions at position 26, 27, 30, 31, or 34 within the transmembrane domain of the matrix-(M)-2 protein. In this study, reverse genetics was used to generate and characterize recombinant influenza A (H1N1) viruses harboring L26F, V27A, A30T, S31N, G34E, and V27A/S31N mutations in the M2 gene. In plaque reduction assays, all mutations conferred amantadine resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 15 publications
2
135
0
1
Order By: Relevance
“…Many amantadineresistant influenza viruses can be selected in cell culture (5,6). A subset of these mutations is found in infected patients undergoing treatment with amantadine (7), and reverse-engineered viruses harboring various pore-lining mutations are competent to replicate in the mouse (8). However, many of these mutations give rise to somewhat attenuated viruses that are less transmissible than WT virus, and they tend to revert in the absence of drug pressure (6,9).…”
Section: M2-s31n Inhibitormentioning
confidence: 99%
“…Many amantadineresistant influenza viruses can be selected in cell culture (5,6). A subset of these mutations is found in infected patients undergoing treatment with amantadine (7), and reverse-engineered viruses harboring various pore-lining mutations are competent to replicate in the mouse (8). However, many of these mutations give rise to somewhat attenuated viruses that are less transmissible than WT virus, and they tend to revert in the absence of drug pressure (6,9).…”
Section: M2-s31n Inhibitormentioning
confidence: 99%
“…1,42 A subset of these mutations are found in infected patients following treatment with amantadine, 43 and reverseengineered viruses harboring various pore-lining mutations are able to replicate in vitro and in a mouse model. 44 However, many of these mutations give rise to somewhat attenuated viruses that are less transmissible than wild-type (WT) and tend to revert in the absence of drug pressure. 42,45 Indeed, large-scale sequencing of transmissible viruses from 1918 to 2010 showed that mutations to pore-lining residues are allowed only within the first turn of the TM helix at positions 26, 27, and 31 [ Fig.…”
Section: Natural and Artificial Sequence Variants Of M2mentioning
confidence: 99%
“…It was previously reported that the serine 31 (S31) cluster is the high-affinity binding site for amantadine (42)(43)(44) and that residues S31 and valine 27 (V27) in M2 confer M2 sensitivity to amantadine (45)(46)(47)(48)(49)(50)(51)(52)(53). Wild-type MX M2 contains residues N31 and V27, while PR M2 contains N31 and threonine 27 (T27) (Fig.…”
Section: M2 Enhances Infectivity Of Ha-pseudovirusmentioning
confidence: 99%